Analysis of the frequency dependency to the single supply differential capacitive sensor - Che Mustapha, Nurul Arfah; Alam, A.H.M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (IEEE, 2018)
This paper presents a single supply differential capacitive sensing technique. Focus is on the analysis of the excitation frequency dependency to the circuit network. First, the theory and derivation of the differential capacitive sensor under test is presented and elaborated. Then, simulation results are shown for comparison. Test was carried out using frequency from 40 kHz up to 400 kHz. Results have shown good linearity of R-squared value 0.99957 at 200 kHz. This capacitive sensor is also suitable to be used for energy harvesting application.